MEKANISME PENGURUSAN LEGALITAS BENTUK DAN KEGIATAN USAHA (Studi Empiris Pada Mahasiswa IIB Darmajaya) - Dian Herlambang (KEADILAN PROGRESIF, 2019)
Progress and increase in national development in general and the development of economic activities in particular have implications for the development of the business worldand companies. Every company that conducts business activities is required to fulfill businessoperational requirements. The legality management mechanism is very necessary to find outhow the procedures for managing the legality of forms and business activities, and whetherDarmajaya IIB students know the mechanism for managing the legality of forms and businessactivities. The purpose of this research is to carry out mapping related to the procedures formanaging the legality of forms and business activities. In addition, this study would like tolook at the practical level regarding the level of knowledge (in this study, the scope is limitedto Darmajaya IIB students) regarding the procedures for managing the legality of forms andbusiness activities. This type of research is normative-empirical legal research, with theapproach used is the socio-legal approach. The legality of the business activity in questionconsists of a Company Register and a Trade Business License. The results of the studyshowed that from 30 people the authors made the subject as a resource person it could besaid that 15 of them answered that they did not know the answer to the question of how themechanism for managing business legality documents.